2005
DOI: 10.1021/es048570c
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Stresses and Skeletal Deformities in Fish from the Willamette River, Oregon

Abstract: The Willamette River, one of 14 American Heritage Rivers, flows through the most densely populated and agriculturally productive region of Oregon. Previous biological monitoring of the Willamette River detected elevated frequencies of skeletal deformities in fish from certain areas of the lower (Newberg pool [NP], rivermile [RM] 26 - 55) and middle (Wheatland Ferry [WF], RM 72 - 74) river, relative to those in the upper river (Corvallis [CV], RM 125-138). The objective of this study was to determine the likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…Nor are such findings restricted to amphibian infections (Cunningham et al. 2005; Villeneuve et al. 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Nor are such findings restricted to amphibian infections (Cunningham et al. 2005; Villeneuve et al. 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Stages of development have been treated similarly in the chick embryo [24], frog [25], and zebrafish [26]. The developmental scores used here (Table 1) were modified from those previously described in Villeneuve et al [27]; a median value was given to intermediate‐staged fish to describe more accurately skeletal development. Healthy 25‐ to 26‐dph juvenile fathead minnows possess a fully ossified vertebral column, with neural and haemal processes projecting from each vertebra (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Kanazawa et al (1981) showed that phospholipids reduced skeletal deformities in larvae of Plecoglossus altivelis and phosphatidy linositol reduced spinal malformations in larval D. labrax (Cahu et al, 2003). On the other hand, excess of phospholipids induced severe skeletal malformations in larval D. labrax (Villeneuve et al, 2005).…”
Section: Discussionmentioning
confidence: 99%